2019
DOI: 10.1111/jon.12653
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐State fMRI Networks in Children with Tuberous Sclerosis Complex

Abstract: BACKGROUND AND PURPOSE:There are no published studies examining resting state networks (RSNs) and their relationship with neurodevelopmental metrics in tuberous sclerosis complex (TSC). We aimed to identify major resting-state functional magnetic resonance imaging (rs-fMRI) networks in infants with TSC and correlate network analyses with neurodevelopmental assessments, autism diagnosis, and seizure history. METHODS: Rs-fMRI data from 34 infants with TSC, sedated with propofol during the scan, were analyzed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 99 publications
1
7
0
Order By: Relevance
“…The evidence of impaired brain connectivity and subtle white matter abnormalities in TSC has broadly confirmed this thesis, with DTI and resting state fMRI (RS-fMRI) suggesting a widespread alteration in axonal organisation and myelination [48]. In particular, two RS-fMRI studies showed the presence of significant differences in functional connectivity between TSC patients and healthy controls, with a more prominent involvement of auditory and motor networks [49,50]. The evidence of altered structural connectivity further validated these functional findings.…”
Section: Role For Advanced Mri Techniques In Tsc-associated Cns Manifsupporting
confidence: 53%
“…The evidence of impaired brain connectivity and subtle white matter abnormalities in TSC has broadly confirmed this thesis, with DTI and resting state fMRI (RS-fMRI) suggesting a widespread alteration in axonal organisation and myelination [48]. In particular, two RS-fMRI studies showed the presence of significant differences in functional connectivity between TSC patients and healthy controls, with a more prominent involvement of auditory and motor networks [49,50]. The evidence of altered structural connectivity further validated these functional findings.…”
Section: Role For Advanced Mri Techniques In Tsc-associated Cns Manifsupporting
confidence: 53%
“…Future applications of the cross-species, multiscale research platform we describe here might help unravel the connectional heterogeneity of ASD by permitting the identification of ASD subtypes 2 . Future case-control imaging investigations of individuals harboring Tsc2 mutations 76 might also crucially help test the validity of our predictions and their mechanistic significance in relevant patient populations.…”
Section: Discussionmentioning
confidence: 95%
“…TSC patients with neuropsychiatric comorbidities had lower structural connectivity. [15,16] To approach models regarding the complex network of brain connectivity, here we intend to apply a graph using the nodes and interconnecting edges to provide measures of whole-brain functional connectivity. [17] The aim is to use resting-state functional connectivity to provide the first findings on the disrupted functional brain networks of TSC patients using graph theoretical analysis (GTA) and network-based statistic (NBS) analysis.…”
Section: Introductionmentioning
confidence: 99%